"Jesuits' epos" in the former capital of the viziers. Gymnasium in Travnik - Moroz-Grzelak, Lilla Janina (Balcanica Posnaniensia. Acta et studia, 2019)
The article focuses on presenting the history of the Jesuit gymnasium in Travnik in the context of socio-political context. . The traces of this education have been preserved in the memories of Miljenko Jergović and by Emir Kusturica. Their short, proud references to the education of their ancestors who attended the gymnasium in Travnik are just a pretext to indicate the circumstances, goals and tasks of the Jesuits who after the restoration of their order after a few decades of dissolution in 1882 opened a school in Travnik and Sarajevo seminary.